2009
DOI: 10.5194/bg-6-2709-2009
|View full text |Cite
|
Sign up to set email alerts
|

Mountain birch – potentially large source of sesquiterpenes into high latitude atmosphere

Abstract: Abstract. Emissions of volatile organic compounds (VOCs) from mountain birches were measured in Abisko, northern Sweden. Mountain birches make up the majority of the tree biomass in Scandinavian high latitudes, a region subject to significant climate warming. The measurements were carried out in two growing seasons. The emissions of four branches, each from a different individual tree, were measured in June–August 2006 and one of them again in July 2007. The measurements were conducted using a dynamic flow thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 34 publications
10
49
0
Order By: Relevance
“…As an example of the emitted compounds, willow (Salix) species, mosses and sedges emit isoprene (Ekberg et al , 2011Rinnan et al 2011b), the crowberry (Empetrum hermaphroditum) sesquiterpenes (Faubert et al 2012), Vaccinium species monoterpenes (Faubert et al 2012), and the dwarf birch (Betula nana L.) and the mountain birch (Betula pubescens ssp. czerepanovii) emit many monoterpenes and sesquiterpenes (Haapanala et al 2009;Rinnan et al 2011b). Although the BVOCs are mainly released from vegetation, soils and microbial processes also contribute to the total ecosystem BVOC emissions (Faubert et al 2012).…”
Section: Emission Of Biogenic Volatile Organic Compounds (Bvocs)mentioning
confidence: 99%
“…As an example of the emitted compounds, willow (Salix) species, mosses and sedges emit isoprene (Ekberg et al , 2011Rinnan et al 2011b), the crowberry (Empetrum hermaphroditum) sesquiterpenes (Faubert et al 2012), Vaccinium species monoterpenes (Faubert et al 2012), and the dwarf birch (Betula nana L.) and the mountain birch (Betula pubescens ssp. czerepanovii) emit many monoterpenes and sesquiterpenes (Haapanala et al 2009;Rinnan et al 2011b). Although the BVOCs are mainly released from vegetation, soils and microbial processes also contribute to the total ecosystem BVOC emissions (Faubert et al 2012).…”
Section: Emission Of Biogenic Volatile Organic Compounds (Bvocs)mentioning
confidence: 99%
“…the white spots, was clearly seen in photographs taken of tree B. Sesquiterpene emissions especially can be related to herbivore attacks the tree may have experienced. Haapanala et al (2009) found large α-farnesene emissions from mountain birches in northern Sweden two years after an outbreak of autumnal moth; when the measurements were repeated the following year, α-farnesene was no longer observed. However, in the case of mechanical or herbivore-attack-induced stress, one expects not only different rates of emissions but also different emission spectra, which were not observed in this study (Haapanala et al, 2009;Duhl et al, 2013).…”
Section: Measured Emission Ratesmentioning
confidence: 99%
“…In some BVOC emission studies done in the northern regions, emissions have been standardized to 20 • C (e.g. Ekberg et al, 2009 andHaapanala et al, 2009). However, as the mean daytime temperature (from 08:00 to 20:00 local time) during the measurement days was 26.8 • C for the first, 26.0 • C for the second and 19.0 • C for the third campaign, the use of a standard temperature of 30 • C is more appropriate.…”
Section: Emission Potential Calculationsmentioning
confidence: 99%
“…But increases in deciduous shrubs could lead to increases in ecosystem BVOC emissions. While Betula species are not isoprene emitters, they do emit monoterpenes and sesquiterpenes (Haapanala et al, 2009;Tarvainen et al, 2007), so increases in Betula species would lead to increases in ecosystem BVOC emissions, assuming that the replaced grasses and sedges had lower emission capacities.…”
Section: Previous Research On Global Change Factors and Deciduous Shrmentioning
confidence: 99%
“…But if non-isoprene-emitting genera like Betula (birch) increase, then ε could decrease for isoprene. The impact on monoterpene and sesquiterpene emission capacities would be the opposite, since Betula is a significant emitter of these chemical compounds (Haapanala et al, 2009). This shift in the emissions profile would have impacts on atmospheric chemistry because of the relatively higher reactivity of these compounds compared to isoprene (see Table 2 in Fuentes et al, 2000).…”
Section: Global Climate Change and Future Emissions From Arctic Ecosymentioning
confidence: 99%